2019
DOI: 10.1186/s12889-019-7484-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with cryptosporidiosis among children within the ages 0–5 years attending the Limbe regional hospital, southwest region, Cameroon

Abstract: Background Cryptosporidiosis is a pathological condition caused by infection with coccidian protozoan parasites Cryptosporidium . Cryptosporidium is one of the most common causes of childhood diarrhea in developing countries. So far, no data has been published on its prevalence among children with diarrhea in Cameroon. This study was therefore, designed to assess the prevalence and risk factors associated with Cryptosporidiosis among children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 28 publications
5
25
3
1
Order By: Relevance
“…Significantly higher prevalence was experienced in females (13.30%) than in males (7.84%) (P=0.000195***), probably because of increased exposure of females to untreated water compared to their male counterparts. This is in line with the results obtained in Uganda by Tombang et al, (2019) who recorded higher prevalence in females (3.3%) than in males. In this study, 97.3% of Cryptosporidium-positive in humans and 79.6% cows and all cases in sheep and goats were observed during the rainy season; between July and December.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Significantly higher prevalence was experienced in females (13.30%) than in males (7.84%) (P=0.000195***), probably because of increased exposure of females to untreated water compared to their male counterparts. This is in line with the results obtained in Uganda by Tombang et al, (2019) who recorded higher prevalence in females (3.3%) than in males. In this study, 97.3% of Cryptosporidium-positive in humans and 79.6% cows and all cases in sheep and goats were observed during the rainy season; between July and December.…”
Section: Discussionsupporting
confidence: 93%
“…Prevalence was higher in the older individuals aged between 41-70 years and children aged between 0 -10 years, and lowest in adolescents aged between 11-20 and adults 20-40 years. These results are similar to those reported in other studies (Hlavsa et al, 2012;Nahed andGhoneim, 2017 andTombang et al, 2019), where incidence and prevalence was found to be highest in children and old age individuals. In this study, the infection rate observed (9.8%) was higher than the prevalence previously reported by Mbae (2006), 4% in children in urban informal settings.…”
Section: Discussionsupporting
confidence: 93%
“…In a study in Gambian children, those consumed stored water, presence of large family size and had contact with animal are at risk of Cryptosporidium infection 17. Another study from Cameron in under five children the presence of diarrhea was reported as concomitant treat for Cryptosporidium infection 18. In addition to this factors undernutrition, having previous hospitalization, older age and living in a day care institution was statically significant associated risk factors reported from Colombian children with HIV-infection 19.…”
Section: Introductionmentioning
confidence: 96%
“… 12 Additionally, poor sanitation and contact with contaminated soil are also risk factors for the development of diarrhea. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The reason of gender based difference is not clear as both male and female children have the same exposure to environment. 13 …”
Section: Discussionmentioning
confidence: 99%